Quercetin: A functional dietary flavonoid with potential chemo‐preventive properties in colorectal cancer - Darband, Saber G.; Kaviani, Mojtaba; Yousefi, Bahman; Sadighparvar, Shirin; Pakdel, Firouz G.; Attari, Javad A.; Mohebbi, Iraj; Naderi, Somayeh; Majidinia, Maryam (Journal of cellular physiology, 2018)
Recently, an intense attention has been paid to the application of natural compounds as a novel therapeutic strategy for cancer treatment. Quercetin, a natural flavonol present in many commonly consumed food items, is widely demonstrated to exert inhibitory effects on cancer progression through various mechanisms. Since there is a strong association with diets containing abundant vegetables, fruits, and grains, and significant decline in the risk of colon cancer, accumulation studies have focused on the anticancer potential of quercetin in colorectal cancer. Cell cycle arrest, increase in apoptosis, antioxidant replication, modulation of estrogen receptors, regulation of signaling pathways, inhibition of and metastasis and angiogenesis are among various mechanisms underlying the chemo‐preventive effects of quercetin in colorectal cancer. This review covers various therapeutic interactions of Quercetin as to how targets cellular involved in cancer treatment. Quercetin, a natural flavonol present in many commonly consumed food items, is widely demonstrated to exert inhibitory effects on cancer progression through various mechanisms. Cell cycle arrest, increase in apoptosis, antioxidant replication, modulation of estrogen receptors, regulation of signaling pathways, inhibition of and metastasis and angiogenesis are among various mechanisms underlying the chemo‐preventive effects of quercetin in colorectal cancer.